JUAL BELI BARANG KADALUARSA DI KOTA PALANGKA RAYA - Khair, Abdul (Jurnal Studi Agama dan Masyarakat, 2011)
The background of the study is that there are practices of sale and purchase of expired goods at city of Palangka Raya although the Law number 8 1999 about the Protection of Consumers (Perlindungan Konsumen) prohibits about those practices which endanger the consumers. The objective of the study is to .know the factors that cause the practices of sale and purchase of expired goods existing in Palangka Raya and how the legal solutions are taken to solves the impacts of the practices of sale and purchase of expired good at Palangka Raya. The method of the study is descriptive qualitative research so that the researcher is able to know and describe what happens in the location of the study clearly and in detailed as well as disclosing the data. Results of the study are in the form of the causes of the practices of sale and purchase of expired goods can be described as follows: (1) the traders do not know that they sell the expired goods while the others sell the expired good intentionally, (2) the lack of direction and control from the government, (3) the limited numbers of personnel of the Regional Office of Industry and Commerce Department, and (4) the traders that are subjected to unannounced inspections of the authority are not given sanctions so that there is no deterrent effect.Â Â